Isolation and Purification of Highly Enriched Tissue Plasminogen Activator from Pig Heart - Rickli, E. E; Zaugg, H (Thrombosis and Haemostasis, 1970)
A method for the isolation of highly purified plasminogen activator from porcine heart was developed. Fresh, frozen tissue was homogenized and extracted with 5 M urea. Upon dilution of the urea extract with 0.02 M acetate buffer, 0.05 M NaCl, pH 5.0, a large amount of inert protein precipitated. It was removed by low-speed centrifugation, leaving an active, cell-free supernatant. CM Sephadex C-50, added to this solution, adsorbed the active material quantitatively. Washing of the ion exchanger with 0.02 M acetate buffer, 0.26 M NaCl, pH 5.0, removed additional impurities. The activator was eluted by increasing the NaCl concentration of the acetate buffer to 0.6 M. Further purification was achieved by a fractionated precipitation with ammonium sulfate at 30% saturation, pH 7.5. The precipitated activator was solubilized in 0.02 M acetate buffer, 0.6 M NaCl, pH 5.0. The resulting active solution was subjected to gel filtration in a column of Sephadex G-200, in the same buffer medium. In this step, a substantial amount of inert, higher molecular weight material was eliminated. The active fractions were pooled and diluted with 0.02 M acetate buffer, pH 5.5, to reduce the NaCl concentration to 0.15 M. This solution was passed through a column of SE Sephadex C-50, in 0.02 M acetate buffer, 0.15 M NaCl, pH 5.5, which adsorbed the active material. The activator was eluted from the column with a salt gradient (0.15 M to 0.4 M NaCl) in 0.02M acetate buffer,pH 5.5. From 3kg of heart tissue, about 1.5 mg of highly purified activator were obtained, in a yield of 35% (with respect to the urea extract). The preparation had a specific activity of 38,900 CTA units per mg protein, determined with a fluorometric assay method, using fluorescence labeled fibrin substrate and a calibration curve with a urokinase standard for conversion of the activity to CTA units. The product was highly stable, and it was devoid of unspecific protease activity. Disc electrophoresis in Polyacrylamide gel at pH 9.5 showed a single sharp band.